Experimental study on unloading induced shear performances of 3D saw-tooth rock fractures - Yin, Qian; Nie, Xinxin; Wu, Jiangyu; Wang, Qi; Bian, Kaiqi; Jing, Hongwen (International journal of mining science and technology, 2023)
A fractal model governing saw-tooth fractures was first introduced to replicate sandstone samples containing an inclined 3D penetrating rough fracture surface with various joint roughness coefficients (JRC). In conventional triaxial compression, the peak strength for fractured samples increased with both confining pressure and JRC. During the unloading confining pressure process, the normal stress of fractures declined but the shear stress increased, resulting in shear sliding of fractures. The shear displacement of fractures exponentially increased, and the positive normal displacement decreased gradually to negative values under coupling effects of shear contraction caused by normal stress and shear dilation due to climbing effects of fractures. Transition from quasi-static to dynamic sliding of the fractures was identified. The sliding resistance duration increased with confining pressure but decreased with JRC. After pre-peak unloading, the fracture surfaces presented a more significant surface wear response and JRC values decreased by 1.70%–59.20% due to more remarkable asperity degradation compared with those after conventional triaxial compression. The theoretical model for shear strength of fractures was established through improving the Ladanyi & Archambault model by introducing the relations between normal stress and surface wear ratios of fractures, which agreed well with the experimental results.